VMT-CNTs / MOF photothermal conversion film and preparation method and application thereof

By growing carbon nano-tube on the base of vermiculite and modifying the metal organic framework, the VMT-CNTS/MOF material is prepared, which solves the problem of the existing light and thermal converting thin film combination. Functional, suitable for seawater dilute, sewage treatment and power generation.

CN119353801APending Publication Date: 2025-01-24TARIM UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411435336.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The bonding between the base material of the existing photothermal conversion film and the photothermal conversion material is poor, resulting in insufficient mechanical strength, and the substrate decomposition or the photothermal conversion material falls off after multiple uses.

Method used

VMT-CNTs/MOF was prepared by peeling off vermiculite (VMT) and reassembling a super-hydrophilic substrate, growing carbon nanotubes (CNTs) in situ on its surface, and modifying the surface of the carbon nanotubes with a metal-organic framework (Cu-MOF). Material.

Benefits of technology

It improves the overall strength and stability of the film, exhibits excellent evaporation performance and hydrovoltaic power generation function, and has cost advantages in seawater desalination, sewage treatment and power generation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119353801A_ABST
    Figure CN119353801A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photothermal conversion materials, and discloses a VMT-CNTs / MOF photothermal conversion film and a preparation method and application thereof. The VMT-CNTs / MOF photothermal conversion thin film comprises a modified expanded vermiculite substrate, carbon nano tubes CNTs grow on the surface of the modified expanded vermiculite substrate in situ, and Cu-MOF is modified on the surfaces of the carbon nano tubes CNTs. According to the preparation method disclosed by the invention, by virtue of excellent photothermal conversion performance of the CTNs and the MOF and super-hydrophilicity of the VMT, the composite material shows strong evaporation performance and has an excellent water photovoltaic power generation function, and the carbon nanotubes (CNTs) grow on a vermiculite substrate in situ, so that the overall strength and stability of the film are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photothermal conversion materials, and more specifically relates to a VMT-CNTs / MOF photothermal conversion film and a preparation method and application thereof. Background Art

[0002] Freshwater resources are an important resource that is indispensable for human survival and development, but the world is currently facing problems such as shortage, pollution and irrational use of freshwater resources. The existing seawater desalination technologies mainly include fossil fuels, electrochemical seawater desalination technology, and membrane technology. However, with the development of time, people began to discover the problems of fossil fuels: serious environmental pollution, greenhouse gases will be produced, leading to global warming, energy consumption is large, and the reserves of fossil fuels are limited, which will become less and less over time. The electrochemical desalination technology mainly extracts water from seawater through electrochemical reactions, but this technology also has environmental pollution and is not easy to promote on a large scale.

[0003] Solar-driven interfacial evaporation is a promising technology for freshwater harvesting due to its high conversion efficiency, great potential for industrial applications, and environmental sustainability. However, this evaporation system is a complex coupled process that is affected by many factors, such as photothermal conversion materials, thermal management, and structural design.

[0004] Chinese patent CN113790538A discloses a photothermal conversion film comprising: a substrate, which is a hydrophilic film; a photothermal conversion material, which is arranged on the surface of the substrate, and the components include at least one of a silicon-based alloy powder and a porous silicon-based powder. The substrate is a glass fiber membrane. The silicon-based alloy powder is prepared into a slurry, coated on the surface of the substrate and dried.

[0005] CN112609465A discloses a method for preparing a wettable material with high thermal conductivity for photothermal conversion. A composite filler with high thermal conductivity and photothermal conversion effect is prepared by in-situ polymerization. The composite filler is then mixed with a silane coupling agent solution and subjected to ultrasonic treatment to form a stable suspension. Secondly, a three-dimensional porous substrate material is immersed in the suspension, and finally dried and solidified to obtain the wettable material. The three-dimensional porous substrate is one of commercial sponge, cotton wool, aerogel, biomass sponge and metal foam.

[0006] Chinese patent CN110726262A discloses a double-layer evaporation structure for solar steam generation, including an upper layer and a lower layer combined together, the upper layer is a photothermal conversion film, and the lower layer is melamine foam; the photothermal conversion film is a CuO@CF photothermal conversion film, or a CuO / Ag@CF photothermal conversion film, and the CuO / Ag@CF photothermal conversion film is a layer of Ag film vacuum-deposited on the CuO film of the CuO@CF photothermal conversion film.

[0007] The photothermal conversion film in the above patents uses coating, infiltration or evaporation to assemble the photothermal conversion material onto the substrate. However, the bonding strength between the film substrate and the photothermal conversion material obtained in this way is poor, the mechanical strength of the substrate material is insufficient, and the substrate decomposes or the conversion material falls off after repeated use.

[0008] Therefore, how to provide a new type of high-strength light-to-heat conversion film is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0009] In order to overcome the shortcomings and deficiencies in the prior art, the present invention prepares VMT-CNTs / MOF materials by stripping and reassembling a super-hydrophilic substrate of vermiculite (VMT), growing carbon nanotubes (CNTs) on its surface in situ, and modifying the metal organic framework (Cu-MOF) on the surface of carbon nanotubes. The composite material exhibits strong evaporation performance and excellent hydrovoltaic power generation function through the excellent photothermal conversion performance of CTNs and MOF and the super-hydrophilicity of VMT. The carbon nanotubes (CNTs) are grown in situ on the vermiculite substrate, which improves the overall strength and stability of the film.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] A VMT-CNTs / MOF light-to-heat conversion film comprises a modified expanded vermiculite substrate, carbon nanotubes CNTs are in-situ grown on the surface of the modified expanded vermiculite substrate, and Cu-MOF is modified on the surface of the carbon nanotubes CNTs.

[0012] The present invention also provides a method for preparing the above-mentioned VMT-CNTs / MOF light-to-heat conversion film, comprising the following steps:

[0013] (1) adding modified expanded vermiculite into deionized water, ultrasonicating, and filtering;

[0014] (2) drying the filtered membrane and placing it in a tubular furnace for calcination;

[0015] (3) placing the calcined film in the high temperature zone of a tube furnace, weighing pyridine and ferrocene, placing them in the low temperature zone of the tube furnace, adjusting the temperature of the tube furnace under a nitrogen atmosphere, and reacting;

[0016] (4) placing the VMT-CNTs in a Cu-MOF precursor solution for hydrothermal reaction, rinsing, and drying.

[0017] Preferably, the mass ratio of the modified expanded vermiculite, pyridine and ferrocene is 1:1.2:0.30 to 1:2:0.35.

[0018] Preferably, in step (2), the calcination temperature is 500-800° C. and the calcination time is 30-40 min.

[0019] Preferably, in step (3), the temperature of the tube furnace is adjusted to 700-800° C. and the reaction is carried out for 3-5 hours; in step (4), the hydrothermal reaction temperature is 45-65° C. and the reaction time is 1-2 hours.

[0020] Preferably, the preparation method of the modified expanded vermiculite comprises the following steps:

[0021] 1) adding expanded vermiculite and sodium chloride into deionized water, heating under reflux after ultrasonication, and washing;

[0022] 2) adding the washed solid phase into a lithium chloride solution, heating under reflux, and washing;

[0023] 3) adding the washed solid phase into a hydrogen peroxide solution, heating to reflux, washing, and drying.

[0024] Preferably, the preparation method of the modified expanded vermiculite specifically comprises the following steps:

[0025] 1) Add 5g of expanded vermiculite and 180g of sodium chloride to 500ml of deionized water, ultrasonicate for 20min, heat in a 90℃ oil bath for 48h, condense and reflux, centrifuge after cooling, and wash the solid phase by centrifugation until there is no chloride ion;

[0026] 2) Add the washed solid phase into 300 ml of 2 mol / L lithium chloride solution, heat in an oil bath at 90°C for 24 h, condense and reflux, centrifuge and wash the solid phase by centrifugation until there are no chloride ions and sodium ions;

[0027] 3) The washed solid phase was added to 200 ml of 30% hydrogen peroxide solution, heated in an oil bath at 110° C. for 24 h, condensed and refluxed, centrifuged, and the solid phase was washed 4-5 times and then dried.

[0028] Preferably, the preparation method of the Cu-MOF precursor solution is: take a CuSO4 solution and a 2,3,6,7,10,11-ethylaminotriphenyl solution, and stir them in a water bath at 40 to 65° C. for 2 to 10 minutes.

[0029] Preferably, the concentration of the CuSO4 solution is 3.8·10-3 mol / L, the concentration of the 2,3,6,7,10,11-ethylaminotriphenyl solution is 5.6·10 -3 mol / L, and the volume ratio of the CuSO4 solution to the 2,3,6,7,10,11-ethylaminotriphenyl solution is 1:1.

[0030] The present invention also provides the application of the above-mentioned light-heat conversion film in solar evaporators, hydrovoltaic power generation, and printing and dyeing wastewater treatment.

[0031] It can be seen from the above technical solutions that, compared with the prior art, the present invention provides a VMT-CNTs / MOF light-to-heat conversion film and a preparation method and application thereof, which have the following beneficial effects:

[0032] The present invention uses vermiculite as the substrate. Natural vermiculite is flaky, hard and dense, and has good cation exchange capacity. Vermiculite has good thermal insulation, heat insulation, moisture retention, adsorption, hydrophilicity and other properties. It also has a high specific surface area and rich pore structure, giving it good water conductivity, which is conducive to improving the evaporation efficiency of the material. The VMT-CNTs / MOF disclosed in the present invention exhibits excellent evaporation performance. Under a solar radiation intensity of (1k·W·m -2 ), the evaporation rate of the prepared solar interface evaporation device is 1.6315 kg·m -2 ·h -1 , evaporation 1.6315kg·m -2 The evaporation efficiency reached 89.41%. Fortunately, it was found that the VMT-CNTs / MOF material used the unidirectional flow of water and the composition characteristics of the material to generate stable voltage and current through organic coupling during the evaporation process. Under a solar radiation intensity of 1k·W·m -2 ), the voltage reached a maximum of 0.29V, the current reached a maximum of 0.02mA, and the power generated during the evaporation process was stable at 25mW·m -2 The present invention utilizes the strong light-concentrating property of VMT-CNTs / MOF materials and the unidirectional flow characteristics of water to simultaneously enhance evaporation performance and power generation performance, so the system shows great cost advantages in seawater desalination applications, sewage treatment applications and power generation applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0034] Figure 1 The infrared spectra of the materials prepared in Example 1 and Comparative Example 1 are as follows;

[0035] Figure 2 XRD patterns of the materials prepared in Example 1 and Comparative Example 1;

[0036] Figure 3 The scanning electron microscope images and elemental analysis images of VMT-CTNs / MOF of each material prepared in Example 1 and Comparative Example 1;

[0037] Figure 4 The Raman spectra of the materials prepared in Example 1 and Comparative Example 1 are as follows;

[0038] Figure 5 The UV-visible light absorption spectra of the materials prepared in Example 1 and Comparative Example 1;

[0039] Figure 6 Infrared thermal imaging images of the materials prepared in Example 1 and Comparative Example 1;

[0040] Figure 7 Comparison of evaporation amount (a) and evaporation rate and evaporation efficiency (b) of various materials prepared at different calcination temperatures;

[0041] Figure 8 Each material prepared in Example 1 and Comparative Example 1 was subjected to a solar radiation (1 k·W·m -2 ) under evaporation amount comparison chart (a) and evaporation rate and evaporation efficiency comparison chart (b);

[0042] Fig. 9 The evaporation amount comparison diagram (a) and the evaporation rate and evaporation efficiency comparison diagram (b) of each material prepared in Example 1 and Comparative Example 1 under different sunlight intensities;

[0043] Fig.10 The cycle diagrams of the materials prepared in Example 1 and Comparative Example 1, where (a) is the VMT-CNTs / MOF cycle diagram and (a) is the VMT-CNTs cycle diagram;

[0044] Fig.11 The evaporation amount and evaporation rate and efficiency diagram of each material prepared in Example 1 and Comparative Example 1 when evaporating salt water of different concentrations;

[0045] Fig.12 The solution conductivity and ion concentration at each stage of evaporating different ion solutions for the VMT-CNTs / MOF material prepared in Example 1;

[0046] Fig.13The evaporation amount and evaporation rate and efficiency of methylene blue solutions of different concentrations evaporated by various materials prepared in Example 1 and Comparative Example 1;

[0047] Fig.14 This is a graph showing the evaporation and temperature data of the VMT-CNTs / MOF material prepared in Example 1 in outdoor environment for 24 hours;

[0048] Fig.15 Electrical performance diagram of the VMT-CNTs / MOF material prepared in Example 1, (a): CV performance test diagram; (b): IT performance test diagram; (c): open circuit voltage data diagram; (d): positive and negative electrode exchange diagram. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Experimental Instruments

[0051] Table 1 Experimental instruments

[0052]

[0053] Experimental reagents

[0054] Table 2 Experimental reagents

[0055]

[0056]

[0057] Example 1

[0058] Preparation method of VMT-CNTs / MOF photothermal conversion film

[0059] 1. Preparation of Modified Expanded VMT

[0060] (1) 10.0 g of raw vermiculite was mixed with 100 ml of deionized water, and the part floating on the water surface was picked out after ultrasonic treatment for 2 h. The washing was repeated 2 to 3 times. The washed vermiculite was spread in a glass container and heated in a 700 W microwave oven for 10 min to prepare expanded VMT. The part floating on the water surface was obtained by flotation.

[0061] (2) 5 g of expanded vermiculite and 180 g of sodium chloride were added to 500 ml of deionized water, and after ultrasonication for 20 min, the mixture was transferred to a 90° C. oil bath and heated for 48 h, condensed and refluxed, and centrifuged (12000 r, 5 min) after cooling. The solid phase was centrifuged and washed until there was no chloride ion, thereby preparing sodium vermiculite and expanding the interlayer distance;

[0062] (3) The washed solid phase is added to a 2 mol / L (25.44 g, 300 ml) lithium chloride solution, heated in an oil bath at 90°C for 24 h, condensed and refluxed, and centrifuged to wash the solid phase until there are no chloride ions or sodium ions. Lithium ions replace sodium ions, further expanding the interlayer distance and increasing the specific surface area.

[0063] (4) The washed solid phase was added to 200 ml of 30% hydrogen peroxide solution, heated in an oil bath at 110° C. for 24 h, condensed and refluxed, centrifuged (12000 r, 5 min), the solid phase was washed 4-5 times, then dried, and the vermiculite flakes were peeled off to form layers.

[0064] 2. Preparation of VMT-CNTs composites

[0065] (1) Weigh 4 g of modified expanded VMT solid phase and add it to 400 ml of deionized water, sonicate for 2 h, and filter the mixed solution;

[0066] (2) drying the filtered membrane and calcining it at 500°C in a tube furnace for 30 min to remove interlayer bound water and increase the strength of the vermiculite membrane;

[0067] (3) The shaped film is then placed in the high temperature zone of a tube furnace. 5 ml (5 g) of pyridine and 1.25 g of ferrocene are weighed and placed in the low temperature zone of the tube furnace. The temperature of the tube furnace is adjusted to 750 °C under a nitrogen atmosphere and the reaction is carried out for 4 h.

[0068] 3. Preparation of VMT-CNTs / MOF composites

[0069] (1) Take 100 ml (3.8·10 -3 mol / L) CuSO4 solution and 100ml (5.6·10 -3 mol / L) 2,3,6,7,10,11-ethylaminotriphenyl solution, stirred in a water bath at 65°C for 2 min to obtain a Cu-MOF precursor solution;

[0070] (2) placing VMT-CNTs in a Cu-MOF precursor solution and reacting at 65°C in a water bath for 2 h for in situ growth;

[0071] (3) Rinse with distilled water and anhydrous ethanol alternately 3-5 times.

[0072] Comparative Example 1

[0073] Preparation method of VMT-MOF photothermal conversion film

[0074] 1. Preparation of Modified Expanded VMT

[0075] (1) 10.0 g of raw vermiculite was mixed with 100 ml of deionized water, and the part floating on the water surface was picked out after ultrasonic treatment for 2 h. The washing was repeated 2 to 3 times. The washed vermiculite was spread in a glass container and heated in a 700 W microwave oven for 10 min to prepare expanded VMT. The part floating on the water surface was obtained by flotation.

[0076] (2) 5 g of expanded vermiculite and 180 g of sodium chloride were added to 500 ml of deionized water, and after ultrasonication for 20 min, the mixture was transferred to a 90° C. oil bath and heated for 48 h, condensed and refluxed, and centrifuged (12000 r, 5 min) after cooling. The solid phase was centrifuged and washed until there was no chloride ion, thereby preparing sodium vermiculite and expanding the interlayer distance;

[0077] (3) The washed solid phase is added to a 2 mol / L (25.44 g, 300 ml) lithium chloride solution, heated in an oil bath at 90°C for 24 h, condensed and refluxed, and centrifuged to wash the solid phase until there are no chloride ions or sodium ions. Lithium ions replace sodium ions, further expanding the interlayer distance and increasing the specific surface area.

[0078] (4) The washed solid phase was added to 200 ml of 30% hydrogen peroxide solution, heated in an oil bath at 110° C. for 24 h, condensed and refluxed, centrifuged (12000 r, 5 min), the solid phase was washed 4-5 times, then dried, and the vermiculite flakes were peeled off to form layers.

[0079] 2. Preparation of Modified VMT

[0080] (1) Weigh 4 g of modified expanded VMT solid phase and add it to 400 ml of deionized water, sonicate for 2 h, and filter the mixed solution;

[0081] (2) The filtered membrane is dried and then calcined at 500°C in a tubular furnace for 30 min to remove interlayer bound water and increase the strength of the vermiculite membrane.

[0082] 3. Preparation of VMT-MOF composites

[0083] (1) Take 100 ml (3.8·10 -3 mol / L) CuSO4 solution and 100ml (5.6·10 -3 mol / L) 2,3,6,7,10,11-ethylaminotriphenyl solution, stirred in a water bath at 65°C for 2 min to obtain a Cu-MOF precursor solution;

[0084] (2) placing the modified VMT into the Cu-MOF precursor solution and reacting it in a water bath at 65°C for 2 h for in situ growth;

[0085] (3) Rinse with distilled water and anhydrous ethanol 3-5 times.

[0086] Test example

[0087] 1. Infrared spectrum detection

[0088] like Figure 1 The infrared spectra of VMT, VMT-CNTs, VMT-MOF, and VMT-CTNs / MOF materials are shown. -1 The peak at 2365 cm-1 corresponds to the stretching vibration of the OH bond. -1 The peak at 1643 cm-1 corresponds to the stretching vibration of the -N=C=O bond. -1 The peak at 1640 cm-1 corresponds to the stretching vibration of the OH bond. -1 The peak at 992 cm-1 corresponds to the stretching vibration of the C=O bond. -1 The peak at 685 cm-1 corresponds to the stretching vibration of the CH bond. -1 The peak at 3443 cm corresponds to the stretching vibration of Al-O. Compared with VMT and VMT-MOF materials, VMT-CNTs and VMT-CNTs / MOF materials lack the peak at 3443 cm -1 The OH bond vibration at 2365 cm -1 -N=C=O bond vibration, 640cm -1 C=O bond vibration and 992cm -1 The excellent hydrophilicity of VMT-CNTs / MOF comes from the hydrophilic groups such as C=O.

[0089] 2. X-ray diffraction detection

[0090] like Figure 2Shown are the XRD patterns of VMT, VMT-CNTs, VMT-MOF, and VMT-CTNs / MOF materials. It can be seen from the figure that the VMT material has strong characteristic peaks at 2θ=8.85° and 2θ=26.59°, and the VMT-MOF material is roughly the same. The VMT-CNTs / MOF material has strong characteristic peaks at 2θ=8.85°, 2θ=26.59°, and 2θ=28.05°, and the VMT-CNTs material is roughly the same. Comparison of the peak values ​​of the four materials proves that the VMT-CNTs / MOF material has a high degree of crystallinity. Compared with VMT-MOF and VMT materials, VMT-CNTs / MOF and VMT-CNTs materials have an extra peak at 2θ=28.05°, which proves that the two substances are successfully composited by in-situ growth of CNTs on VMT.

[0091] 3. Scanning electron microscope detection

[0092] like Figure 3 The following are the scanning electron micrographs of VMT, VMT-CNTs, VMT-MOF, and VMT-CTNs / MOF materials. The microscopic morphology of the materials was observed and analyzed by scanning electron microscopy. Figure 3 (a) is a SEM image of VMT-CNTs at 100 μm. The VMT is on the right side of the image. It can be observed that VMT is a layered substance, while the film is formed by stacking many VMTs together. Figure 3 (b) is the SEM photo of VMT-CNTs at 100 μm. On the left, it can be seen that the VMT is evenly covered with CNTs. Figure 3 (c) is a high-magnification image of Figure b. Figure 3 (b) SEM photo of the framed position at 5 μm. Figure 3 (c) shows that CNTs are tubular and evenly distributed; Figure 3 (d) is the SEM image of VMT-CNTs / MOF at 50 μm. Figure 3 In (d), it can be clearly seen that CNTs and MOF are in an upper-lower layer relationship, proving that MOF is successfully composited onto CNTs; Figure 3 (e) is the SEM image of VMT-CNTs / MOF at 10 μm. Figure 3 In (e), it can be observed that the distribution of MOF is very uniform and the growth is good; Figure 3 (f) Figure 3 (e) SEM photo of the framed position at 1 μm. Figure 3 (f) shows that the MOF has a regular uniform columnar shape, and its monomer width is 0.2 μm. Its elemental analysis is Figure 3(e) Elemental analysis of the framed position. Through its elemental analysis, it can be seen that MOF is uniformly modified on CNTs and successfully composited on VMT.

[0093] 4. Raman spectroscopy detection

[0094] Depend on Figure 4 The Raman spectra of VMT, VMT-MOF, VMT-CNTs, and VMT-CNTs / MOF materials are shown. Compared with VMT and VMT-MOF materials, VMT-CNTs and VMT-CNTs / MOF have more D-band and G-band, which proves that the materials are successfully composited with CNTs. The I D / I G is 1.52; I of VMT-CNTs material D / I G The value of CNTs / MOF is 2.60, which proves that the structure of CNTs after compounding with MOF is relatively complete and the lattice quality is relatively high. Compared with VMT-CNTs material, VMT-CNTs / MOF material has an additional 2D-band, which proves that the CNTs in the VMT-CNTs / MOF material exist in a stacking manner with fewer layers.

[0095] 5. UV-Visible light absorption detection

[0096] The material's ability to absorb sunlight is the key to determining evaporation performance, such as Figure 5 The UV-visible light absorption spectra of VMT-MOF, VMT-CNTs, and VMT-CNTs / MOF materials are shown. The light absorption of VMT-MOF material drops sharply between 250nm and 800nm, and stabilizes at 0.2W·m after 800nm. -2 ·nm -1 The light absorption of VMT-CNTs material in the range of 250nm-1000nm is higher than that of VMT-CNTs / MOF material. The light absorption of the two materials in the range of 1000nm-1800nm ​​is basically the same, while the light absorption of VMT-CNTs / MOF material in the range of 1800nm-2500nm is significantly stronger than that of VMT-CNTs material. This proves that the composite of CNTs and MOF on VMT has a great effect on enhancing the light absorption capacity.

[0097] 6. Infrared thermal imager test

[0098] Figure 6The infrared thermal images of VMT-MOF, VMT-CNTs, and VMT-CNTs / MOF materials are shown. Through the infrared imager, the temperature of the evaporation material surface and the temperature of the water in the evaporation device can be seen intuitively, proving that the thermal insulation material has a more obvious effect. Under the sunlight of one sun, the surface of the evaporation material heats up rapidly. The VMT-CNTs temperature rises the fastest, reaching a maximum value of 37.9°C at 35 minutes. The temperature rise of VMT-CNTs / MOF is second only to VMT-CNTs, and the final temperature is 38.3°C, which is higher than VMT-CNTs. The VMT-MOF material heats up the slowest, and the final temperature is 37.5°C, which is the slowest and lowest among the three materials. Therefore, the material with the best light-to-heat conversion effect among the three materials is VMT-CNTs / MOF.

[0099] 7. Temperature gradient experiment

[0100] like Figure 7 As shown in the figure, under one sun, through the temperature gradient experiment, the evaporation amount (a), evaporation rate and evaporation efficiency (b) of the sample obtained by changing the calcination temperature according to the method of Example 1 are compared. The experimental temperatures are 600℃, 650℃, 700℃, 750℃, 800℃ and the blank experiment respectively. During the experiment, it is found that its evaporation performance shows a trend of first increasing and then decreasing, reaching the highest value at 700℃, with an evaporation amount of 1.4920kg·m -2 , the evaporation rate is 1.4920 kg·m -2 ·h -1 The evaporation efficiency reached 81.83%. Through comparative analysis of experimental data, it can be seen that the material calcined at 700°C has the best evaporation performance, which can effectively improve the light focusing property of the material while having the least effect on its hydrophilicity, so the optimal temperature of the experiment is 700°C.

[0101] 8. Evaporation test

[0102] like Figure 8 (a) shows the comparison of the evaporation of VMT-MOF, VMT-CNTs, and VMT-CNTs / MOF at room temperature (28 °C). -2 ) are 1.2741 kg·m -2 , 1.4920kg·m -2 , 1.6315kg·m -2 . Figure 8 (b) is a comparison of the evaporation rates and evaporation efficiencies of VMT-MOF, VMT-CNTs, and VMT-CNTs / MOF. -2) were 68.70%, 81.83% and 89.41% respectively. Figure 8 From the data analysis, it can be seen that VMT-CNTs / MOF material has the best evaporation performance.

[0103] 9. Evaporation test under different sunlight intensities

[0104] As the light intensity increases, the surface temperature of the evaporation material and the vapor temperature also increase. In order to explore the relationship between light intensity and evaporation performance, a solar gradient experiment was designed. The test temperature was room temperature (28°C). Fig. 9 (a) Evaporation amount of VMT-CNTs / MOF under different light intensities; Fig. 9 (b) Evaporation rate and efficiency of VMT-CNTs / MOF under different light intensities. The evaporation amount is 1.6315 kg·m under 1 sun. -2 , the evaporation rate is 1.6315 kg·m -2 ·h -1 , the evaporation efficiency is 89.41%; under 5 sun conditions, the evaporation capacity is 6.0883 kg·m -2 , the evaporation rate is 6.0883 kg·m -2 ·h -1 , the evaporation efficiency is 78.40%.

[0105] Fig. 9 (c) Evaporation amount of VMT-CNTs under different light intensities; Fig. 9 (d) Evaporation rate and efficiency of VMT-CNTs under different light intensities. The evaporation amount is 1.4920 kg·m under 1 sun. -2 , the evaporation rate is 1.4920 kg·m -2 ·h -1 , the evaporation efficiency is 81.83%; under 5 sun conditions, the evaporation capacity is 5.5670 kg·m -2 , the evaporation rate is 5.5670 kg·m -2 ·h -1 , the evaporation efficiency is 71.70%.

[0106] Fig. 9 (e) Evaporation amount of VMT-MOF under different light intensities; Fig. 9 (f) Evaporation rate and efficiency of VMT-MOF under different light intensities. Under 1 sun, the evaporation amount is 1.2741 kg·m -2 , the evaporation rate is 1.2741 kg·m -2 ·h -1 , the evaporation efficiency is 68.70%; under 5sun, the evaporation capacity is 3.8644kg·m -2, the evaporation rate is 3.8644 kg·m -2 ·h -1 , the evaporation efficiency is 48.93%.

[0107] The evaporation rate can be used as a basis for evaluating the water production of the evaporation device per unit time, while the evaporation efficiency can be used to evaluate the photothermal conversion effect of the evaporation material. The evaporation efficiency under the corresponding light intensity is calculated using formula (3). It can be concluded that the photothermal conversion effect and evaporation performance of the VMT-CNTs / MOF material are the best under 1 sun. Under the condition of continuous enhanced light, the evaporation performance of the VMT-CNTs / MOF material is least affected, and its evaporation efficiency is still maintained at 78.40% under 5 suns. It can be concluded that the VMT-CNTs / MOF material has the best light intensity resistance.

[0108] 10. Cyclic Experiment

[0109] Fig.10 This is a cyclic experiment diagram. Fig.10 As shown in (a), the evaporation of VMT-CNTs / MOF during the cyclic experiment is roughly maintained at a constant value in 10 cycles, and the evaporation of each cycle is 1.9 kg·m -2 It can be seen that the performance of the VMT-CNTs / MOF evaporation device is very stable. Fig.10 (b) is the cycle diagram of VMT-CNTs after 8 cycles. By observing the data, it can be seen that the evaporation amount in each cycle is maintained at 1.5 kg·m -2 The data comparison proves that the composite MOF on VMT-CNTs can improve the evaporation performance of the material without destroying its stability.

[0110] 11. Experiment on evaporation performance of salt water with different concentrations

[0111] like Fig.11The figure shows the evaporation performance test of salt water of different concentrations (3.5wt%, 7wt%, 12wt%) of each sample. The test was carried out at room temperature (28℃). Figure (a) is the evaporation amount of salt water of different concentrations evaporated by VMT-CNTs / MOF, and Figure (b) is the evaporation rate and efficiency of salt water of different concentrations evaporated by VMT-CNTs / MOF. In the figure, we can observe that the evaporation amount decreases with the increase of salt water concentration, which shows that the increase of salt water concentration will affect the evaporation performance of the material; Figure (c) is the evaporation amount of salt water of different concentrations evaporated by VMT-CNTs, and Figure (d) is the evaporation rate and efficiency of salt water of different concentrations evaporated by VMT-CNTs. In the figure, we can observe that the increase of salt water concentration will affect the evaporation performance; Figure (e) is the evaporation amount of salt water of different concentrations evaporated by VMT-MOF, and Figure (f) is the evaporation rate and efficiency of salt water of different concentrations evaporated by VMT-MOF. From Figures (e) and (f), we can see that the evaporation performance is limited by the concentration of salt water. By observing the six figures (a), (b), (c), (d), (e) and (f), we can find that VMT-MOF and VMT-CNTs are more affected by salt water than VMT-CNTs / MOF materials, which proves that VMT-CNTs / MOF materials are more suitable for seawater evaporation than the other two materials.

[0112] 12. Seawater simulation experiment

[0113] The ion composition of seawater in the southeastern coastal area of ​​my country is Na + Mg 2+ , Ca + , K + Four major ions, different ion agriculture formulated to mimic the composition of seawater, Fig.12 (a) The conductivity of the initial, distilled water, and solution at the end of evaporation of different ion solutions from VMT-CNTs / MOF materials, as well as the conductivity of tap water. The test temperature was room temperature (28°C). Na + The conductivity was 55.04mS / cm at the beginning and 55.90mS / cm at the end. The conductivity of the distilled water was 80.02μS / cm. Mg 2+ The conductivity was 4565μS / cm at the beginning and 8251μS / cm at the end. The conductivity of the distilled water was 56.11μS / cm. 2+ The conductivity was 2138μS / cm at the beginning and 3460μS / cm at the end. The conductivity of the distilled water was 77.14μS / cm. + The conductivity was 1037μS / cm at the beginning and 1383μS / cm at the end. The conductivity of the distilled water was 86.64μS / cm. Fig.12(b) The initial and distilled water ion concentrations of different ion solutions evaporated from VMT-CNTs / MOF materials. + The initial ion concentration of the solution was 57.05 μmol / l, and the distilled water was 0.08 μmol / l; the evaporated Mg 2+ The initial ion concentration of the solution is 4.73 μmol / l, and the distilled water is 0.06 μmol / l; the evaporated Ca 2+ The initial ion concentration of the solution is 2.22 μmol / l; the distilled water is 0.08 μmol / l; the evaporated K + The initial ion concentration of the solution is 1.07μmol / l, and the distilled water is 0.09μmol / l. From the data, we can see that the VMT-CNTs / MOF material has an excellent filtering effect on ions. The conductivity of the evaporated water is much lower than the 1014μS / cm of tap water. According to the "Drinking Water Hygiene Standard GB579-2006", the conductivity range of drinking water is usually between 0-50μS / cm. The evaporated water meets the reference standard, proving that the material has an excellent barrier effect on ions in seawater.

[0114] 13. Experiment on evaporation of methylene blue solutions of different concentrations

[0115] Fig.13 The figure shows the experiment of evaporating methylene blue solutions of different concentrations (0 mg / L, 1 mg / L, 3 mg / L, 5 mg / L). Figure (a) shows the evaporation amount of methylene blue solutions of different concentrations evaporated by VMT-CNTs / MOF material. Figure (b) shows the evaporation rate and efficiency of methylene blue solutions of different concentrations evaporated by VMT-CNTs / MOF. By observing the figure, we can see that the evaporation performance of the material is affected by the increase of the concentration of methylene blue solution. Figure (c) shows the evaporation amount of methylene blue solutions of different concentrations evaporated by VMT-CNTs material. Figure (d) shows the evaporation rate and efficiency of methylene blue solutions of different concentrations evaporated by VMT-CNTs. From the figure, we can see that the methylene blue concentration has a significant effect on the evaporation performance. Figure (e) shows the evaporation amount of methylene blue solutions of different concentrations evaporated by VMT-MOF material. Figure (f) shows the evaporation rate and efficiency of methylene blue solutions of different concentrations evaporated by VMT-MOF material. From the figure, we can see that the concentration of methylene blue solution has a significant effect on it. By observing the six figures (a), (b), (c), (d), (e), and (f), we can conclude that the VMT-CNTs / MOF material is relatively less affected by the methylene blue solution, so the VMT-CNTs / MOF material is more suitable for sewage treatment than the other two materials.

[0116] 14.24h outdoor evaporation performance experiment

[0117] like Fig.14 The figure shows the evaporation and temperature data of VMT-CNTs / MOF material outdoors for 24 hours. The experimental location is (E: 81.29°; N: 40.54°). In the figure, we can see that the evaporation and temperature increase rapidly after 10:00. This is because the light intensity increases with time after the sun appears, reaching a maximum value of 1.6075 kg·m at 17:00. -2 At this time, the light intensity is the strongest. After 20:00, the sun begins to set, so the evaporation also begins to drop sharply. After the sun completely sets, the evaporation tends to stabilize and reaches the lowest value of 0.2190 kg·m at 8:00 in the morning. -2 Through analysis, it can be seen that the evaporation is less affected by temperature than by light, and the evaporation is more obviously affected by temperature when there is no light. Therefore, it can be judged that the evaporation is not only affected by light but also by temperature.

[0118] 15. Electrical performance experiment

[0119] like Fig.15 The electrical properties of VMT-CNTs / MOF materials are shown in Figure (a) at a scan rate of 20 mV·S -1 Figure (b) is the CV performance test diagram, the maximum current generated during evaporation is 0.02mA when measured with an ohmmeter. Figure (b) is the IT performance test diagram, the current generated during the evaporation process is stable at 12.73mA·m -2 , the voltage is stable at 0.20 V, and the power generated during the evaporation process is calculated by formula (4) to be stable at 25 mW·m -2 It can be proved that VMT-CNTs / MOF materials generate stable current and voltage during evaporation, and the power is also very stable. Figure (c) is the open circuit voltage data diagram of VMT-CNTs / MOF materials distilling pure water and 3.5% salt water. It can be seen from Figure (c) that the voltage generated when evaporating pure water is the largest and the voltage is the most stable. Figure (d) is the positive and negative electrode exchange diagram of the open circuit voltage generated when VMT-CNTs / MOF materials distill pure water. It can be seen from Figure (d) that the maximum value of the open circuit voltage is 0.29V, and each section of the open circuit voltage is very stable. It proves that VMT-CNTs / MOF materials can generate stable and continuous open circuit voltage.

[0120] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the scheme disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0121] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A VMT-CNTs / MOF light-to-heat conversion film, characterized in that: The VMT-CNTs / MOF light-to-heat conversion film comprises a modified expanded vermiculite substrate, carbon nanotubes CNTs are in-situ grown on the surface of the modified expanded vermiculite substrate, and Cu-MOF is modified on the surface of the carbon nanotubes CNTs.

2. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 1, characterized in that: The following steps are involved: (1) adding modified expanded vermiculite into deionized water, ultrasonicating, and filtering; (2) drying the filtered membrane and placing it in a tubular furnace for calcination; (3) placing the calcined film in the high temperature zone of a tube furnace, weighing pyridine and ferrocene, placing them in the low temperature zone of the tube furnace, adjusting the temperature of the tube furnace under a nitrogen atmosphere, and reacting; (4) placing the VMT-CNTs in a Cu-MOF precursor solution for hydrothermal reaction, rinsing, and drying.

3. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 2, characterized in that: The mass ratio of the modified expanded vermiculite, pyridine and ferrocene is 1:1.2:0.30 to 1:2:0.

35.

4. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 2, characterized in that: In step (2), the calcination temperature is 500-800° C. and the calcination time is 30-40 min.

5. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 4, characterized in that: In step (3), the temperature of the tube furnace is adjusted to 700-800° C. and the reaction is carried out for 3-5 hours. In step (4), the hydrothermal reaction temperature is 45-65° C. and the reaction time is 1-2 hours.

6. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 4, characterized in that: The preparation method of the modified expanded vermiculite comprises the following steps: 1) adding expanded vermiculite and sodium chloride into deionized water, heating under reflux after ultrasonication, and washing; 2) adding the washed solid phase into a lithium chloride solution, heating under reflux, and washing; 3) adding the washed solid phase into a hydrogen peroxide solution, heating to reflux, washing, and drying.

7. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 4, characterized in that: The preparation method of the modified expanded vermiculite specifically comprises the following steps: 1) Add 5g of expanded vermiculite and 180g of sodium chloride to 500ml of deionized water, ultrasonicate for 20min, heat in a 90℃ oil bath for 48h, condense and reflux, centrifuge after cooling, and wash the solid phase by centrifugation until there is no chloride ion; 2) Add the washed solid phase into 300 ml of 2 mol / L lithium chloride solution, heat in an oil bath at 90°C for 24 h, condense and reflux, centrifuge and wash the solid phase by centrifugation until there are no chloride ions and sodium ions; 3) The washed solid phase was added to 200 ml of 30% hydrogen peroxide solution, heated in an oil bath at 110° C. for 24 h, condensed and refluxed, centrifuged, and the solid phase was washed 4-5 times and then dried.

8. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 4, characterized in that: The preparation method of the Cu-MOF precursor solution is as follows: taking a CuSO4 solution and a 2,3,6,7,10,11-ethylaminotriphenyl solution, stirring them in a water bath at 40 to 65° C. for 2 to 10 minutes.

9. The method for preparing a VMT-CNTs / MOF light-to-heat conversion film according to claim 8, characterized in that: The concentration of the CuSO4 solution is 3.8·10 -3 mol / L, the concentration of the 2,3,6,7,10,11-ethylaminotriphenyl solution is 5.6·10 -3 mol / L, and the volume ratio of the CuSO4 solution to the 2,3,6,7,10,11-ethylaminotriphenyl solution is 1:

1.

10. Application of the photothermal conversion film according to claim 1 or the photothermal conversion film prepared by the preparation method according to any one of claims 2 to 9 in solar evaporators, hydrovoltaic power generation, and printing and dyeing wastewater treatment.

Citation Information

Patent Citations

  • Photothermal conversion film, preparation method thereof and double-layer evaporation structure for solar steam generation

    CN110726262A

  • Photo-thermal conversion high-thermal-conductivity wettable material and preparation method thereof

    CN112609465A

  • Photo-thermal conversion film and preparation method and application thereof

    CN113790538A